Intraoperative Optical Coherence Tomography-guided 25G Microamount Trajectory Vitrectomy for the Treatment of Penetrating Ocular Injury Caused by a Foreign Body in the Right Eye: A Case Study - Wang, Yuan; Wang, Shengyu; Zhao, Xingxing; Lu, Xin; Wang, Tiantian; Chen, Wenjun; Du, Zhaojiang (Current Medical Imaging, 2022)
Background: Optical coherence tomography (OCT) is a real-time three-dimensional tomography optical imaging technology that uses near-infrared waves to take cross-sectional pictures of the retina and other tissues. A few studies have reported the use of intraoperative OCT navigation for the removal of foreign bodies from the eyeball during surgery. The objective is to present a single case with a small foreign body (not embedded in the retina) treated with intraoperative OCT guided 25G micro-amount trajectory vitrectomy. Case Presentation: The examination of a 25-year-old man, who suffered from right eye pain, suggested the following: the visual acuity was 20/250, the intraocular pressure was 8 mmHg, a scleral penetrating wound was visible at 3 mm behind the limbus at 7 o' clock, and Tyn (+). The vitreous showed some flocculent turbidity, the retina was flat, and the foreign body was visible at 10 o' clock. On the day of admission, the patient underwent a micro-amount vitrectomy with the removal of the foreign body. The vitreous body affected by the foreign body was then removed through the original wound track by using intraoperative OCT navigation. Conclusion: The final follow-up showed the best-corrected vision of the right eye as 20/25 andno occurrence of complications. The intraoperative OCT-guided 25G micro-amount trajectory vitrectomy could be used as an accurate, useful, and safe method for foreign body extraction.
Keywords: ICL